The Position Of Prepositional Constructions In The Sentence In Modern English (Eurasian Journal of Humanities and Social Sciences, 2024)
This article describes prepositions pose a challenge to the learners as well as teachers of English because of the uniqueness of the problem involved. The learners face difficulties in the proper usage of prepositions in sentences, and therefore, land in trouble. Besides that, each of these prepositions has various meanings and usages that make the learning process equally difficult. In English, many prepositions are used to describe both spatial and temporal relationships. The article presents theoretical ideas in this regard and proves them with examples.